2019
DOI: 10.18203/2349-3933.ijam20193621
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life at six months after primary percutaneous coronary intervention performed at a predominantly rural population

Abstract: Background: HRQL is important in improving the quality of patient care. However, there is a paucity of data from low-income and middle-income countries (LMIC). Differences in socio-demographics and socio-cultural contexts may influence HRQOL. Therefore, this research was designed with the aim to explore the HRQOL in patients after Percutaneous Coronary Intervention (PCI).Objective: The goal of the study was to evaluate the quality of life after six months of Percutaneous Coronary Intervention using HeartQol qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…The findings of this investigation were confirmed with those of earlier studies. Previous studies also showed that female patients scored lower HRQoL than men (Jankowska-Polańska et al, 2016;Mujtaba et al, 2019). Males showed a positive trend for improvement in the majority of HRQoL categories, whereas females improved only in the Physical Component Summary and social functioning domains (Jankowska-Polańska et al, 2016).…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…The findings of this investigation were confirmed with those of earlier studies. Previous studies also showed that female patients scored lower HRQoL than men (Jankowska-Polańska et al, 2016;Mujtaba et al, 2019). Males showed a positive trend for improvement in the majority of HRQoL categories, whereas females improved only in the Physical Component Summary and social functioning domains (Jankowska-Polańska et al, 2016).…”
Section: Discussionmentioning
confidence: 78%
“…Older patients reported higher levels of angina scores one year after acute MI than younger patients (<50 years) (Arnold et al, 2014). Patients commonly experience recurrent angina after PCI, particularly patients with diffuse coronary artery disease involving more than one artery (Mujtaba et al, 2019). However, PCI significantly improved angina stability, frequency, and physical limitation (Ybarra et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…In the last four decades, cardiac rehabilitation (CR) has come to be considered an essential part of the management of patients suffering from CAD. While studies are abundant globally, in the regional context, there are very few studies from South Asia exploring the mortality and morbidity of cardiac patients adhering to rehabilitation programs along with medical and surgical management [4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…PCI has demonstrated a tremendous reduction in mortality and has allowed for early discharges [ 3 ]. Furthermore, it also improved the quality of life in patients with myocardial infarction [ 4 ]. Reintegration into society and return to pre-disease health status nevertheless continues to be a public health problem.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation